2016
DOI: 10.2298/vsp140917148c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atorvastatin and artichoke leaf tincture on oxidative stress in hypercholesterolemic rats

Abstract: Separate treatments comparison showed that artichoke leaf tincture is very potent antioxidant with beneficial effects in early stages of atherosclerosis. Since atorvastatin and constituents of ALTINC probably have different mechanisms of action, simultaneous use of both therapies could be beneficial but should be further investigated since our results showed that ALTINC is less effective when used in combination with atorvastatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…These results showed that ATV treatment could protect ovary injury against the side effects of CP. ATV at low dose is well known for its antioxidant and anti-inflammatory properties (10, 11). It is suggested that ATV through antioxidant property may have protective role and improve the antioxidant status of the ovary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results showed that ATV treatment could protect ovary injury against the side effects of CP. ATV at low dose is well known for its antioxidant and anti-inflammatory properties (10, 11). It is suggested that ATV through antioxidant property may have protective role and improve the antioxidant status of the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…ATV addition to lowering cholesterol level, has therapeutic beneficial pleiotropic effects that happen at low dose (9). Biological and pharmacological properties of ATV are anti-inflammatory (10) antioxidant properties (11). On the other hand, high-dose atorvastatin is associated with many complications such as nephrotoxicity (12), testicular injury (13).…”
Section: Introductionmentioning
confidence: 99%
“…CA is present in a variety of plants as intermediary in secondary metabolism. It is found in coffee, wine and olive oil; worldwide, popular antiobesity uses have been traditionally attributed to this polyphenolic compound (Wider et al, 2013;Rondanelli et al, 2014;Crevar-Sakac et al, 2016;Rangboo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Аналогічні результати отри-мані в іншому рандомізованому подвійному сліпому плацебо-контрольованому клінічному дослідженні на 39 пацієнтах молодого віку (21-55 років), де зниження рівня ЛПНЩ складало 21 % та тригліцеридів -14 % [25]. До висновку щодо перспективності ЕА в якості антиатеро-склеротичного засобу приходять і інші дослід-ники [22,26].…”
unclassified
“…Так, у порівняльному вивченні на моделі окси-дативного стресу у гіперхолестеромічних щу-рів за 6 тижнів прийому аторвастатину і ЕА було продемонстровано позитивний ефект на тов-щину стінки абдомінальної аорти та параметри оксидативного стресу (малондіальдегід, прокси-датив-антиоксидатив-баланс) та антиоксидант-ного захисту (знижений глютатіон -GSH, пара-оксигеназа 1 -PON1, супероксиддисмутаза -SODA SH). Слід відмітити, що у комбінації з атор-вастатином екстракт артишоку був менш актив-ним, ніж індивідуально, що свідчить про віро-гідно схожі механізми дії цих двох засобів [26]. У той же час при комбінованому застосуванні препаратів часнику з симвастатином у проспек-тивному рандомізованому подвійному сліпому дослідженні за участю 258 пацієнтів з дисліпі-демією за 8 тижнів ліпідні показники крові були достовірно покращеними на тлі застосування такої комбінації порівняно з групою симвастати-ну.…”
unclassified